The shark house : a novel - Ackerman, Sara (Harper Muse, 2026)
"People aren't the only ones who migrate to Hawai'i for a warmer winter. 1998. In the heart of paradise, danger lurks beneath the surface. Biologist and shark whisperer Minnow Gray travels to the rugged Hawai'i coastline, where a series of shark attacks have left the island community on edge. Tasked with uncovering what's going on, she dives into the blue depths, and discovers the problem runs deeper than just one dangerous great white. Haunted by her own past marked by a tragic shark encounter, Minnow finds herself drawn into a tangled web of intrigue and peril that extends far beyond the ocean's surface. A scandal that implicates some of the island's most powerful people. Determined to uncover the reason for these attacks before the mayor calls a mass killing of sharks in the area, Minnow forms an unexpected alliance with enigmatic fisherman Luke Greenwood whose presence ignites feelings she can't ignore, but also stirs questions about his part in it all. As Minnow works to shield the sharks from the island's fear-fueled backlash, drawing help from two Hawaiian brothers who are housing her, she unravels a scandal that shakes the community to its core. But it's not just the secrets of the island that rise to the surface. Minnow must confront her own traumatic past, the haunting memories that have shaped her life and her connection to these misunderstood predators--and to this place." --